Maternal work hours in early to middle childhood link to later adolescent diet quality - Li, Jianghong; O'Sullivan, T.; Johnson, S.; Stanley, F.; Oddy, W. (Cambridge University Press, 2011)
Objective: Previous studies on maternal work hours and child diet quality have reported conflicting findings possibly due to differences in study design, lack of a comprehensive measure of diet quality and differing ages of the children under investigation. The present study aimed to prospectively examine the impact of parental work hours from age 1 year to age 14 years on adolescent diet quality. Design: Multivariate linear regression models were used to examine independent associations between parents’ work hours at each follow-up and across 14 years and adolescent diet quality at age 14 years. A diet quality index was based on the international literature and Australian recommendations, consisting of six food groups and nine nutrients. Setting: Perth, Western Australia. Subjects: Children (n 1629) participating in the Western Australian Pregnancy Cohort (Raine) Study. Results: Compared with children of mothers in full-time employment, children of mothers who were not employed in early childhood up to age 5 years had a higher average diet quality score at age 14 years, independent of maternal and family socio-economic status. Across 14 years the number of years the mother worked full time and increasing average weekly hours were associated with lower diet quality. Father’s work hours had little association with adolescent diet quality. Conclusions: Having a mother stay at home in early to middle childhood is associated with better diet quality in adolescence. Support may be beneficial for families where the mother returns to full-time employment before the child reaches 8 years of age.